The Influence of Parasocial Relationships on Celebrity Credibility and Consumer Behavior Before and After a TV Show Finale - Bugarin, Renzo Josh M. (Animo Repository, 2022)
Parasocial relationships (PSR) are characterized by the feeling of intimacy or personal connection by media consumers to media characters through one-sided interactions. In recent years, studies revealed that people have become increasingly dependent on online personas or celebrities to seek comfort and fulfill self-indulgent interactions during the pandemic. However, previous literature on PSR fails to monitor the development of investigated factors over impactful changes in the media such as the airing of a finale. This study is therefore conducted to fulfill two main objectives: a) to determine the relationship of PSR with celebrity credibility and consumer behavior and b) to investigate whether there is a significant difference in these relationships pre- and post-finale. The study adopted a causal-comparative design and utilized a survey questionnaire distributed to engaged adult viewers of La Casa De Papel (LCDP) before and after the finale. The survey measured the levels of the media consumers’ intensified celebrity attachment, perceived celebrity credibility, and influenced personal preferences, which are notable effects of PSRs. Results indicated that the show has not promoted high PSR levels among its Filipino audience. Furthermore, the airing of the LCDP series finale did not make any significant impact on the viewers in all the collected measures of pre-test and post-test PSR. Nevertheless, it is clear that LCDP may have attracted a large pool of viewers, but the relationship of the characters with its viewers has not elevated to a high level of parasocial relationship but remains in the conventional behavioral characteristic of a fan.